2017
DOI: 10.1002/nau.23268
|View full text |Cite
|
Sign up to set email alerts
|

Re: Sheng W, Zhang H, Kirschner‐Hermanns R. Could urinary nerve growth factor be a biomarker for overactive bladder? A meta‐analysis. Neurourol Urodyn. 2017;9999:1–8. doi: 10.1002/nau.23210

Abstract: Sheng et al (Neurourology and Urodynamics 2017; DOI: 10.1002/nau.23210) presented a meta-analysis based on 17 publications to show that urinary nerve growth factor (NGF) may be a useful biomarker for overactive bladder syndrome (OAB). Unfortunately, 13 of the 17 studies used an unspecifc enzyme-linked immunosorbent assay (ELISA), the Promega NGF Emax Immunoassay, to quantify NGF in urine. This assay did not detect NGF in urine, but other urinary components, such as immunoglobulin G, and in 2014, it was withdra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…One of the most important is the limited sensitivity of current ELISA technology for determining urinary BDNF and NGF concentrations. In their letter to the editor on a meta-analysis on the usefulness of NGF as a biomarker in urine OBA, Gamper and Viereck emphasise that many studies used ELISA kits from Promega (Promega, Madison, USA) that were later shown to quantify urine components other than NGF and were therefore withdrawn from the market (25). They also refer to two of the above-mentioned studies in which NGF concentrations were below the limit of detection, which is consistent with our study (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important is the limited sensitivity of current ELISA technology for determining urinary BDNF and NGF concentrations. In their letter to the editor on a meta-analysis on the usefulness of NGF as a biomarker in urine OBA, Gamper and Viereck emphasise that many studies used ELISA kits from Promega (Promega, Madison, USA) that were later shown to quantify urine components other than NGF and were therefore withdrawn from the market (25). They also refer to two of the above-mentioned studies in which NGF concentrations were below the limit of detection, which is consistent with our study (20,21).…”
Section: Discussionmentioning
confidence: 99%